APPLYING THE OPTIMAL METHOD OF DETERMINING THE INTERSECTION OF TWO PLANES - Kayumov X. A; Kamilzhonov N (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article highlights the role of Engineering Computer Graphics in the development of creativity in students. The article covers the importance, purpose, content, and advantages of teaching the development of creativity to students of higher education institutions through the science of Engineering Computer Graphics